2015
DOI: 10.1007/s00125-015-3569-9
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in or near ZNRF1, COLEC12, SCYL1BP1 and API5 are associated with diabetic retinopathy in Chinese patients with type 2 diabetes

Abstract: Aims/hypothesis Three recent genome-wide association studies (GWAS) identified several single-nucleotide polymorphisms (SNPs) with modest effects on diabetic retinopathy in Mexican-American and white patients with diabetes. This study aimed to evaluate the effects of these variants on diabetic retinopathy in Chinese patients with type 2 diabetes. Methods A total of 1,972 patients with type 2 diabetes were recruited to this study, including 819 patients with diabetic retinopathy and 1,153 patients with diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…[4][5][6][7][8]10,19,21,22,24,28,30,34,[38][39][40][42][43][44][47][48][49][50][51][52][53] 69 This is consistent with other genome-wide association studies in Caucasian and Mexican-American patients. 70,71 As the relationship between genetic polymorphisms and diabetic retinopathy is still a new and emerging field, some studies have demonstrated new associations between single nucleotide polymorphisms, but these studies have not yet been replicable.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…[4][5][6][7][8]10,19,21,22,24,28,30,34,[38][39][40][42][43][44][47][48][49][50][51][52][53] 69 This is consistent with other genome-wide association studies in Caucasian and Mexican-American patients. 70,71 As the relationship between genetic polymorphisms and diabetic retinopathy is still a new and emerging field, some studies have demonstrated new associations between single nucleotide polymorphisms, but these studies have not yet been replicable.…”
supporting
confidence: 89%
“…Investigating the polymorphisms associated with diabetic retinopathy may help us better understand the developmental pathway of diabetic retinopathy and lead to new targeted therapy in treating diabetes and preventing diabetic retinopathy. [69][70][71] rs6427247 near SCYL1BP1 Unmodifiable Positive rs6427247 near SCYL1BP1 positively associated with increased risk of severe diabetic retinopathy [69][70][71] rs899036 near API5 Unmodifiable Positive rs899036 near API5 positively associated with increased risk of severe diabetic retinopathy [69][70][71] …”
Section: Discussionmentioning
confidence: 99%
“…The API5 protein suppresses apoptosis induced by the transcription factor E2F1, and interacts with and negatively regulates Acinus, a nuclear factor involved in apoptotic DNA fragmentation. The API5 gene is involved in many human diseases including diabetes and cancers (Cho et al, 2014; Noh et al, 2014; Peng et al, 2015; Ramdas et al, 2011). However, API5 has not been reported to be involved in skeletal muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…ZNRF1 (Zinc and ring finger 1, E3 ubiquitin protein ligase) is an E3 ubiquitin-protein ligase that mediates the ubiquitination of AKT1 and glutamate-ammonia ligase (GLUL), playing a role in neuronal cell differentiation. ZNRF1 regulates neurodegeneration, maintenance of neuronal transmission, plasticity, and Schwann cell differentiation in DR [62].…”
Section: Neurogenesismentioning
confidence: 99%